Medico-social substantiation of the concept of personalized medicine in the prevention of arterial hypertension among the adult population at the regional level - Lashkul, Z. V.; Lashkul, D. A.; Лашкул, Дмитро Андрійович (My University, 2021)
The aim: Is to scientifically substantiate the concept of personalized medicine in the prevention of arterial hypertension (AH) among the adult population at the regional level. Materials and methods: The study, after obtaining informed consent, involved 2000 patients, residents of Zaporizhzhia Region, including 1000 patients (average age 59±0.5 years, the ratio of men to women 1:1.22 people) with and 1000 patients (average age of whom is 62±0.7 years, the ratio of men to women is 1:1.1) without AH. The data of the sociological survey were processed, the methods of mathematical modeling, statistical, system analysis were applied. Odds ratio (OR) is determined by generally accepted methods with the calculation of 95% of confidence interval (CI). Results: The application of the concept of personalized medicine in the prevention of AH among the adult population has been scientifically substantiated by studying the associations between medical and social risk factors and the development of AH and determining on their basis 3 modules – “risk behavior”, “adverse health factors” and “social determinants of the development of AH”, based on stepwise multiple logistic regression analysis. Conclusions: It has been proved that the use of the final prognostic model of the development of arterial hypertension with the inclusion of the most significant risk factors has high operational characteristics: sensitivity – 78.6%, specificity – 96.6%, positive predicative value – 95.85%, negative predicative value – 81.86%, the area under the ROC curve is 0.9623. The application of the concept of personalized medicine in the prevention of this disease among the adult population was substantiated by studying the associations between medical and social risk factors and the development of arterial hypertension.
Lashkul D. A. - ORCID: 0000-0001-7802-3550
Keywords: risk factors; arterial hypertension; personalized medicine